Over and Over, and Over Again: Tension, Repetition, and Catharsis in the Films of Wes Anderson. Issue 2 (1st September 2021) - Stringer, Michael
This article argues that Wes Anderson's films repeat formal and thematic strategies in such a way that resists traditional auteurist analysis. By looking at Anderson's recognizable style of image composition, his expansive paratext, and recurring thematic motifs, we can see a productive system of repetition operative both within and across his films. The value Anderson places on repetition opposes Peter Wollen's structural auteurist framework, which values variation over repetition. Such opposition allows Anderson's films to be taken up as a critique of this valuation, demonstrated through an analysis of the productive role of repetition in his work.